Condições de acessibilidade em habitação de interesse social: estudo de caso em condomínios par em Passo Fundo - Furlanetto, Claudia Helena Paim (2013)
The present work addresses the applicability of public policies for social housing (habitação de interesse social HIS) accessibility in order to contribute to the effectuation of this right in the housing space built. The object of the case study is housing from the Residential Leasing Program (Programa de Arrendamento Residencial PAR) of Passo Fundo and the conditions of access routes for residents to the main community facilities around them. The methodological procedures were given in two phases: on the first phase bibliographical and legislation researches were performed on the theme of accessibility; on the second one, a diagnosis of housings was performed through documental and field researches with technical evaluation and users opinion, using the method of post occupation evaluation (análise pós-ocupação APO), so to examine accessibility in the referred spaces and around them. Next, comparisons were made between the current situation, legislation, and technical requirements, with discussion of results. The results show agreement between the technical evaluation and user satisfaction evaluation in the scaling of walkways and surroundings, as well as external and building areas. Regarding the surroundings, although there are some attempts for ramps, they do not allow the movement of handicap and people with reduced mobility. In accessing community facilities, it is noted the non-existence of accessible routes in the neighborhood and in the city, moreover, many public community facilities do not have building accessibility. Internal, external, and urban signaling is another item not contemplated, indicating again the disregard and neglect from the public sector with the enforcement of the available legislation. Finally, recommendations were proposed for new works or adaptations in social housings